Melittin - the main component of bee venom: a promising therapeutic agent for neuroprotection through keap1/Nrf2/HO-1 pathway activation - Cong Duc Nguyen; Jaehee Yoo; Sang Jun Jeong; Hai-Anh Ha; Ji Hye Yang; Gihyun Lee; Jeong Cheol Shin; Jae-Hong Kim (BMC, 2024)
Abstract The Nuclear factor erythroid 2-related factor (Nrf2)/ Heme oxygenase-1 (HO-1) pathway, known for its significant role in regulating innate antioxidant defense mechanisms, is increasingly being recognized for its potential in neuroprotection studies. Derived from bee venom, melittin's neuroprotective effects have raised interest. This study confirmed that melittin specificity upregulated the weakened Nrf2/HO-1 signaling in mice brain. Interestingly, we also revealed melittin's efficient tactic, as it was suggested to first restore redox balance and then gradually stabilized other regulations of the mouse hippocampus. Using a neuro-stress-induced scopolamine model, chromatography and mass spectrometry analysis revealed that melittin crossed the compromised blood-brain barrier and accumulated in the hippocampus, which provided the chance to interact directly to weakened neurons. A wide range of improvements of melittin action were observed from various tests from behavior Morris water maze, Y maze test to immune florescent staining, western blots. As we need to find out what is the focus of melittin action, we conducted a careful observation in mice which showed that: the first signs of changes, in the hippocampus, within 5 h after melittin administration were the restoration of the Nrf2/HO-1 system and suppression of oxidative stress. After this event, from 7 to 12.5 h after administration, a diversity of conditions was all ameliorated: inflammation, apoptosis, neurotrophic factors, cholinergic function, and tissue ATP level. This chain reaction underscores that melittin focus was on redox balance's role, which revived multiple neuronal functions. Evidence of enhancement in the mouse hippocampus led to further exploration with hippocampal cell line HT22 model. Immunofluorescence analysis showed melittin-induced Nrf2 translocation to the nucleus, which would initiating the translation of antioxidant genes like HO-1. Pathway inhibitors pinpointed melittin's direct influence on the Nrf2/HO-1 pathway. 3D docking models and pull-down assays suggested melittin's direct interaction with Keap1, the regulator of the Nrf2/HO-1 pathway. Overall, this study not only highlighted melittin specifically effect on Nrf2/HO-1, thus rebalancing cellular redox, and also showed that this is an effective multi-faceted therapeutic strategy against neurodegeneration.